2016
DOI: 10.5351/csam.2016.23.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial: Methodologies for sufficient dimension reduction in regression

Abstract: In the paper, as a sequence of the first tutorial, we discuss sufficient dimension reduction methodologies used to estimate central subspace (sliced inverse regression, sliced average variance estimation), central mean subspace (ordinary least square, principal Hessian direction, iterative Hessian transformation), and central k thmoment subspace (covariance method). Large-sample tests to determine the structural dimensions of the three target subspaces are well derived in most of the methodologies; however, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the other hand, in Figure 8, it is observed that the second sufficient predictors from KIR and FHIR with 3, 6 and 9 clusters are highly correlated to each other, so we expect that the structural dimension determination for KIR and FHIR should be, at least, two following the same rationale in Yoo (2018). To investigate this, a permutation dimension test (Yin and Bura, 2006;Yoo, 2016b) were conducted for FHIR and FpSIR, and weighted χ 2 test for KIR (Setoji and Cook, 2004) starting H 0 : d = 0 with nominal level 5%. If H 0 : d = 0 is not rejected, increment d by 1 and redo the test.…”
Section: Minneapolis School Datamentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in Figure 8, it is observed that the second sufficient predictors from KIR and FHIR with 3, 6 and 9 clusters are highly correlated to each other, so we expect that the structural dimension determination for KIR and FHIR should be, at least, two following the same rationale in Yoo (2018). To investigate this, a permutation dimension test (Yin and Bura, 2006;Yoo, 2016b) were conducted for FHIR and FpSIR, and weighted χ 2 test for KIR (Setoji and Cook, 2004) starting H 0 : d = 0 with nominal level 5%. If H 0 : d = 0 is not rejected, increment d by 1 and redo the test.…”
Section: Minneapolis School Datamentioning
confidence: 98%
“…Letting Σ = cov(X), Li (1991) showed that Yoo (2016b). In practice, E(Z|Y) is restored instead of E(X|Y).…”
Section: Sliced Inverse Regressionmentioning
confidence: 99%
“…In SDR context, it is normally assumed that S(E(Z|Y)) = S Z|Y . For more about the two conditions mentioned here, readers are recommended to read Yoo (2016aYoo ( , 2016b. Hereafter without mentioning clearly, we assume that S(E(Z|Y)) = S Y|Z .…”
Section: Sliced and Fused Sliced Inverse Regressionsmentioning
confidence: 99%
“…The response is sliced for each category or to have equal numbers of observations (although it is not strictly required). Readers are recommended to read Yoo (2016aYoo ( , 2016b for further insights about SDR and details on SIR and SAVE.…”
Section: Introductionmentioning
confidence: 99%